The impact of transformational leadership towards organization citizenship behavior: case study human resource development center of ministry of energy and mineral resources - Prasetya Gusman, Dimas; Hamid Batubara, Abdul (The Indonesian Journal of Business Administration, 2018)
Abstract. With the fast progressing demand of high competence human resources in the sector energy mineral resource, Human Resources Development Center- Ministry of (HRDC-EMR) must increase its organization performance to achieve competitive advantages.  The  variables to increase the organization performance are including the leader behavior (leader’s technique and style) and organization citizenship behavior. The aim of the study is to find the fundamental relationship of transformational leadership and organizational citizenship behavior in HRDC-EMR, how it impacted each other, and proposes business solution to increase the quality of transformational leadership and organizational citizenship behavior. The quantitative methods were used to gather and evaluate the data using an investigation survey with the distribution of questionnaires. Multiple regressions were used to evaluate the relationship between transformational leadership and organizational citizenship behavior.  The  results  of  this  study show that there  is  a  positive  and  significant  relationship  between transformational leadership and organizational citizenship behavior.  Along with the finding, this study provides a recommendation as a business solution to improve the transformational leadership and organizational citizenship behavior for the betterment of the HRDC-EMR in the future.Keywords: Human Resources, Organization Performance, Transformational Leadership, Organizational Citizenship Behavior